2019
DOI: 10.3126/jcmsn.v15i1.21128
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Acceptability of Cervical Cancer Screening among Adult Women Visiting in Gynecological OPD

Abstract: Background: Cervical cancer is the most common form of cancer among women developing countries. Pap smear is a very significant screening test for reduction of incidence and mortality from cervical cancer. The pap smear test  detect precancerous cell change on the cervix that might become cervical cancer if they are not treated appropriately. The objective of this research is to find out the knowledge and acceptability of cervical cancer screening among adult women. Methods: A cross-sectional research de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…The study of Shrestha BK et al, where, majority (58.1%) of the respondents had good knowledge in cervical cancer screening and 66.4% of the respondent accepted Pap smear test. Study showed the association between respondents knowledge of cervical cancer screening with educational status (p=0.04), religion (p=0.01) at 0.05 level of significance [15]. A study from India by Narayana G et al, revealed that most (74.6%) of the respondents had heard about cervical cancer and majority of them are heard from media (41.6%).…”
Section: Discussionmentioning
confidence: 94%
“…The study of Shrestha BK et al, where, majority (58.1%) of the respondents had good knowledge in cervical cancer screening and 66.4% of the respondent accepted Pap smear test. Study showed the association between respondents knowledge of cervical cancer screening with educational status (p=0.04), religion (p=0.01) at 0.05 level of significance [15]. A study from India by Narayana G et al, revealed that most (74.6%) of the respondents had heard about cervical cancer and majority of them are heard from media (41.6%).…”
Section: Discussionmentioning
confidence: 94%
“…A similar cross-sectional study was conducted to assess the level of knowledge and acceptability of cervical cancer screening among 425 adult women visiting gynecological OPD of Bharatpur Hospital. A result shows that 58% had good knowledge of cervical cancer screening 66.4% of respondents had good knowledge of Pap smear tests and 33.6% had poor knowledge [11] as given in Table 5.…”
Section: Level Of Knowledge Scorementioning
confidence: 98%